Urgency of Tax Incentives in Indonesia for Research, Development, and Internationalization of MSMEs - Sudarmanto, Eko; Aulia, Triana Zuhrotun; Putri, Rumanintya Lisaria; Wulandjani, Harimurti (PT. Riset Press International, 2024)
The purpose of this research is to reveal and find out some of the factors needed by micro, small and medium enterprises (MSMEs) to develop their business through development research in order to increase economic growth and business networks at the international level. This study uses library research methods, through a qualitative approach with deductive and inductive process analysis. The data source is secondary data, namely relevant previous scientific work. Data processing is done by: analyzing correlations and building concepts to predict, explain, and control the studied phenomena, and draw conclusions based on the theoretical framework. The results of this study indicate that the development of MSME entrepreneurship is the main driver of economic growth in several countries, including Indonesia. For the development of MSMEs, the government can provide a conducive environment for the business world and MSMEs through financial support such as providing tax incentives. So that MSME development research is the main focus in innovation and technological change to increase higher economic growth. Improving the performance of MSMEs through innovation, job creation, export growth, and the emergence of new highly competitive entrepreneurs is an opportunity to gain greater access to new markets at the international level.